On the early-age bond-slip behavior of an eccentric bar embedded in a grouted sleeve. (1st July 2019) - Xu, Tengfei; Li, Quanwen; Zhao, Renda; Ding, Jiancai; Zhan, Yulin
Highlights: The local and global bond-slip behavior of grouted sleeve connection was tested. The eccentricity impaired the confinement effect of grouted sleeve connection. The influence of the construction eccentricity was mitigated by a longer bond length. Analytical model was used to assess the bond-slip behavior of global bond specimens. Abstract: Grouted-sleeve connections are widely used to connect prefabricated concrete members. The bond stress-slip behavior is an essential issue to be considered when assessing the performance of a grouted-sleeve connection loaded in tension. This paper presents an experimental investigation regarding the local and global bond stress-slip behavior of grouted-sleeve connections. Three parameters were investigated: the embedment length, construction eccentricity, and loading time after grouting, respectively. The specimens were subjected to a monotonic tensile load, and the slip between the bar and the grouted-sleeve was measured during the test. Moreover, to evaluate the confinement effect, the circumferential strain at the surface of the grouted-sleeve was measured. The results reveal that the maximum local bond stress increases with the age of the grout, whereas it decreases as the construction eccentricity of the bar increases. Moreover, the influence of the construction eccentricity is mitigated by a longer bonded length. The load-slip relationship is approximately linear for the specimen with an embedment length-to-bar diameter ratio equal to ten, loaded at the age of seven days. Based on the experimental results, an analytical model, including the local and global bond stress-slip relationship, is proposed to evaluate the maximum slip and to describe the strain distribution in the long specimens ( l b / d  = 6, 10). The agreement among the experimental and calculated bond stress, the maximum slip and strain distribution at the surface of the sleeve demonstrates the validity of the proposed model.